HUBUNGAN KOMPENSASI DENGAN KINERJA DOSEN STAIN TEUNGKU DIRUNDENG MEULABOH - Purnamasari, Laras; Herman, Herman; Hardianty, Sri (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
One of the dominant factors in increasing lecturer performance is the compensation they receive. Performance or work performance of lecturers is the result achieved by a lecturer in carrying out the tasks assigned to him based on skills, experience, and seriousness as well as responsibility and use of time. This research is a field research (field Research), with the research subject is STAIN Teungku Dirundeng Meulaboh lecturer. Data collection techniques through questionnaires, while data analysis techniques using linearity test techniques using SPSS for windows version 20. The results showed that the significance value (Sig) of the output above obtained a Deviation from Linearity Sig value of 0.488 or greater than 0.05 and the F value of the output above was 0.938 (Fcount) or smaller than 4.18 (Ftable). Because the Deviation from Linearity Sig value and the Fcount value are smaller than Ftable, it can be concluded that there is a significant linear relationship between compensation and the performance of STAIN Teungku Dirundeng Meulaboh.